(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Empire of the Incas is one of the oldest empires in the American continent. This empire grew and flourished on the continent. It witnessed greatness and glamour in the arts of construction, sculpture, engraving, drafting, ceramics, literature, writing, calculus, astronomy and mythology ,and it was equal to the civilizations of the ancient world, and surpassed it in some areas. With the advent of the European invasion of the continent ,this civilization was hit and attacked by a group of savage adventurers whose aim was to steal gold and precious wealth. It was eliminated, and its temples and civilization were destroyed. and the extermination of its inhabitants in the most extreme forms of genocide. A number of factors paved the way for the Spanish to occupy and eliminate this empire completely. The most important of these factors: civil war between the kings, which ended shortly before the arrival of the Spaniards. Thus, the unity that made the Enquies so much military power disintegrated before the arrival of the Spanish. The second factor was the rapid spread of European diseases throughout the Andean region. These epidemics, such as measles, smallpox, typhoid fever and influenza, were transmitted by the Spaniards to Mexico during their conquests in that region beginning in 1519. These diseases spread south through the indigenous Central American population, and eventually reached Peru. The indigenous people of the original world had no resistance to these diseases, and they were fed up with them. In some areas, up to 90% of the population died, leaving survivors’ diseases psychologically injured.